Effect of Problem-Based Learning Model on Learning Outcomes in Microeconomic Course - Saut Maruli Tua Pandiangan; Josua Alexander Gultom; Dian Ariani; Donny Dharmawan; Ribka Sari Butar-Butar (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this research is to analyze effect of problem-based learning model on learning outcomes in microeconomic course. The approach used in this research is a quantitative approach. Population in this study are students from Medan City Private Universities. Due to the large population, sample is determined randomly, namely 50 respondents. The data analysis technique in this research uses simple linear regression analysis. The research results show that problem-based learning model has a positive and significant effect on learning outcomes in microeconomic course.